World directory of minorities - Anderson, Bridget; Minority Rights Group (London : Minority Rights Group International, 1997)
The World Directory of Minorities is an authoritative, concise and up-to-date reference book on the contemporary situation of ethnic, linguistic and religious minorities worldwide. Covering more than 200 states and dependent territories, and over 700 minority groups, this region-by-region and country-by-country study provides a coherent and wide-ranging introduction to international, regional and local minority rights issues, complete with key bibliographical references and listings of organizations active in the field.
Preface / Alan Phillips -- Introduction to the Directory / Miles Litvinoff -- 1. North America / Alex Roslin and Carl Wilson -- 2. Central and South America and the Caribbean / Patrick Costello, Lindsey Crickmay and James Ferguson -- 3. Western Europe / Bridget Anderson -- 4. Central and Eastern Europe / Martyn Rady and Bogdan Szajkowski -- 5. The Commonwealth of Independent States / Anna Matveeva, Neil Melvin and Suzanne Pattle -- 6. The Middle East / David McDowall -- 7. North, West and the Horn of Africa / Julia Maxted and Abebe Zegeye -- 8. Central and Southern Africa / Chris Dammers and David Sogge -- 9. South Asia / Javaid Rehman and Nikhil Roy -- 10. East and South-East Asia / James Chin, David Hawk and Peter O'Neill -- 11. Oceania / John Connell -- Contemporary Legal Standards on Minority Rights / Patrick Thornberry -- Appendix. Basic Documents on Minorities and Indigenous Peoples / Edited by Patrick Thornberry.
"Second edition"--P. [xiv].
Includes bibliographical references and index.
Keywords: Ethnic groups -- Encyclopedias; Minorities -- Encyclopedias